Histological evaluation of thermal damage to Osteocytes: A comparative study of conventional and ultrasonic-assisted bone grinding. (April 2021) - Babbar, Atul; Jain, Vivek; Gupta, Dheeraj; Agrawal, Deepak
Highlights: Osteotomy has been performed on skull bone using ultrasonic-assisted bone grinding. Cellular responses to temperature increase during grinding as a function rotational speed, feed rate, and frequency, have been studied. The results revealed that ultrasonic-assisted bone grinding caused higher density of filled lacunae compared to conventional grinding. Histological analysis revealed that vibrational grinding can mitigate the death of bone cells. Abstract: This paper addresses an important issue faced by neurosurgeons during surgical skull bone grinding, a common process used to remove bone in skull base tumour removal surgery to enable the neurosurgeon to reach the target region. The heat generated during bone grinding could harm the soft tissues and can lead to osteonecrosis and cell death. In the present study, a novel process of rotary ultrasonic bone grinding (RUBG) was proposed for osteotomy to limit the temperature to a safe level. A systematic investigation was conducted to determine the effect of varying process parameters on osteonecrosis at the cut surface. Three input parameters - rotational speed, feed rate and frequency – were investigated (at three levels) in terms of change in temperature and thermal biological damage. A sterile solution was used as a coolant to irrigate the grinding zone. Viable lacunae (filled osteocytes), non-viable lacunae (empty lacunae), necrosed tissues, and Haversian canal were found during the histological examination. Statistical analysis revealed that feed rate (45.43%) had the highest contribution towards temperature rise during grinding, followed by ultrasonic frequency (23.87%), and rotational speed (12.85%). The optimal machining parameters to avoid osteonecrosis and thermal trauma were rotational speed 35, 000 rpm, feed rate 20 mm/min and ultrasonic frequency 20 kHz. Furthermore, histograms revealed that ultrasonic skull bone grinding was associated with greater cell viability and reduced temperature compared with conventional bone grinding.